A domestic robotic rehabilitation device for assessment of wrist function for outpatients. (November 2020) - Panny, Matthias; Mayr, Andreas; Nagiller, Marco; Kim, Yeongmi
Introduction: Available robot-assisted stroke rehabilitation systems are often limited in their utilization in the home environment, due to several barriers such as high cost, absence of therapists, tedious training tasks, or encumbering interfaces. This paper presents a low-cost robotic rehabilitation and assessment device for restoring wrist function, offering wrist exercises incorporating pronation-supination and flexion-extension movements. Furthermore, the device is designed for the assessment of joint stiffness of the wrist, and range of motion in two degrees of freedom.Methods: Mechanical/electrical design of the device as well as the control system is described. A preliminary evaluation focused on the measurement of the torsional stiffness of the limb is presented. It is evaluated by reconstructing the known stiffness values of torsional springs by measuring the motor current required to displace them. Results: The device demonstrates the ability to determine the stiffness of an object with low-cost hardware. Use case scenarios of the device for training and assessment of the wrist are presented, allowing for a range of motion of± 75 ° and± 65 °, for pronation-supination and flexion-extension respectively. Conclusion: The device shows potential to help objectively quantify the stiffness of the wrist movement, which consecutively could be used to represent and quantify the degree of impairment of patients after stroke in a more objective manner. Further clinical study is necessary to examine this.